Effect of Clinical Typing on Serum Urate Targets of Benzbromarone in Chinese Gout Patients: A Prospective Cohort Study - Xue, Xiaomei; Yuan, Xuan; Han, Lin; Li, Xinde; Merriman, Tony R.; Cui, Lingling; Liu, Zhen; Sun, Wenyan; Wang, Can; Yan, Fei; He, Yuwei; Ji, Aichang; et al. (Frontiers in Medicine, 2022)
Introduction Achieving a goal of serum urate levels in patients with gout is an important way to prevent gout and its complications while it remains difficult with a low targeting rate worldwidely. Currently, hyperuricemia classification has not been widely applied to the management of gout owing to insufficient clinical evidences. This study aimed to evaluate the effectiveness of achieving target urate based on hyperuricemia classification in Chinese patients with gout. Methods In this prospective study, patients with gout receiving urate lowering therapy with benzbromarone were assigned to two groups, a renal underexcretion and an unclassified type. The primary endpoint was the proportion of patients achieving the serum urate target (<360 μmol/L) during the 12-week study. The frequency of acute gout attacks as well as physical and chemical indicators were secondary endpoints. Results Target serum urate level was achieved in 60.5% of underexcretors compared with 39.0% of patients of the unclassified type at week 12 (P = 0.002). Blood glucose and cholesterol levels were lower in the underexcretor group compared with the unclassified type group at the end of the trial, without significant different frequencies in gout flare during the study. In subgroup analysis, stratified by body mass index and estimated glomerular filtration rate, the proportion of patients with serum urate <360 μmol/L was greater in the underexcretion compared with the unclassified type group. Conclusions The increased achievement of target serum urate in the underexcretion group supports the use of a clinical hyperuricemia typing treatment strategy for gout.